Flavonoids from Macaranga lowii - Widiastuti Agustina; Lia D. Juliawaty; Euis H. Hakim; Yana M. Syah (Institute for Research and Community Services (LPPM) ITB, 2012)
A new isoprenylated dihydroflavonol derivative, macalowiinin (1), together with two known flavonoids 4'-O-methyl-8-isoprenylnaringenin (2) and 4'-O-methyl-5,7,4'-trihydroxyflavone (3) (= acasetin), have been isolated from the methanol extract of the leaves of Macaranga lowii. The structures of these compounds were determined based on UV, NMR, and mass spectral data, and optical rotation. Preliminary cytotoxic evaluation of compounds 1